Next: Convergence
Up: Regularization from significant structures
Previous: Regularization of the one-step
Regularization of Lucy's algorithm
Now, define
I(n)(x,y) = P(x,y) * O(n) (x,y). Then
R(n)(x,y) = I(x,y) - I(n)(x,y), and
hence
I(x,y) = I(n)(x,y) + R(n)(x,y).
Lucy's equation is:
![$\displaystyle O^{(n+1)}(x,y) = O^{(n)}(x,y) [ \frac{I^{(n)}(x,y) +
R^{(n)}(x,y)}{I^{(n)}(x,y)} * P(-x,-y) ]$](img865.gif) |
|
|
(14.119) |
and the regularization leads [39] to:
![$\displaystyle O^{(n+1)}(x,y) = O^{(n)}(x,y) [ \frac{I^{(n)}(x,y) +
{\bar{R}}^{(n)}(x,y)}{I^{(n)}(x,y)} * P(-x,-y) ]$](img866.gif) |
|
|
(14.120) |
Petra Nass
1999-06-15